The Effect of Ownership Structure on Firm Value with Profitability as a Moderating Variable - Rohim, Muhammad; Syamsudin, S; Satriawi, Swara Prabu Windy (Universitas Muhammadiyah Surakarta, 2019)
This study aims to analyze the effect of the Ownership Structure on Firm Value which is moderated by profitability. The population is used by manufacturing companies listed on the Indonesia Stock Exchange during 2014-2018. The sample in this study amounted to 625 companies. The sampling technique using purposive sampling method. Data analysis techniques using Moderated Regression Analysis (MRA), F test, t-test and the coefficient of determination test (R2). The results of this study indicate that: 1) Foreign Institutional Ownership has a significant negative effect on firm value. 2) Domestic Institutional Ownership has a significant negative effect on firm value. 3) Public ownership does not significantly influence the value of the company. 4) Managerial Ownership has a negative and significant effect on the value of the company. 5) Profitability has a significant negative effect on company value, 6) Profitability can moderate between foreign institutional ownership to the value of the company, 7) Profitability can moderate between Domestic Institutional Ownership to firm value, 8) Profitability cannot moderate public ownership against company value, 9) Profitability cannot moderate between managerial ownership and firm value.